2018
DOI: 10.1103/physrevapplied.10.034052
|View full text |Cite
|
Sign up to set email alerts
|

Strain-Mediated Spin-Orbit-Torque Switching for Magnetic Memory

Abstract: Spin-orbit torque (SOT) represents an energy efficient method to control magnetization in magnetic memory devices. However, deterministically switching perpendicular memory bits usually requires the application of an additional bias field for breaking lateral symmetry. Here we present a new approach of field-free deterministic perpendicular switching using a strain-mediated SOT switching method. The strain-induced magnetoelastic anisotropy breaks the lateral symmetry, and the resulting symmetry-breaking is con… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 51 publications
0
17
0
1
Order By: Relevance
“…This principle of SOT switching acceleration is similar to existing proposals of the strain- [27][28][29] or charge-accelerated [30] spintransfer torque magnetization switching. Furthermore, a strain-induced uniaxial magnetic anisotropy may also enable a magnetic-field-free SOT out-of-plane magnetization switching when the axis of the effective field is misaligned with the net spin polarization, according to a recent computational study [31] . Despite these exciting prospects, experimental reports on the strain-mediated SOT devices in magnetoelectric heterostructures have remained elusive.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This principle of SOT switching acceleration is similar to existing proposals of the strain- [27][28][29] or charge-accelerated [30] spintransfer torque magnetization switching. Furthermore, a strain-induced uniaxial magnetic anisotropy may also enable a magnetic-field-free SOT out-of-plane magnetization switching when the axis of the effective field is misaligned with the net spin polarization, according to a recent computational study [31] . Despite these exciting prospects, experimental reports on the strain-mediated SOT devices in magnetoelectric heterostructures have remained elusive.…”
mentioning
confidence: 99%
“…This is consistent with a recent computational study (ref. 31) which has suggested that a straininduced uniaxial magnetic anisotropy may enable a magnetic-field-free perpendicular SOT magnetization switching when the strain-induced uniaxial magnetic anisotropy is misaligned with the net spin polarization. Resonance field H FMR as a function of the applied electric fields for the magnetization oriented at both 45° and 135° relative to the current direction.…”
mentioning
confidence: 99%
“…The exchange bias field H eb is estimated to be approximately 470 Oe. Additionally, the magnetization switching of the RL is not modulated by the E-field, as shown in the shaded light green in Figure 8D because the SAF structure provides a strong RKKY interaction for the RL (Wang et al, 2018a(Wang et al, , 2018b. From the magnetic hysteresis loop along the minor axis (the [01-1] direction of the PMN-PT substrate), the magnetic switching becomes easier after applying an E-field of 6 kV/cm, as shown in Figure S13A in the supplemental information.…”
Section: Ll Open Access Isciencementioning
confidence: 99%
“…Bandyopadhyay et al (Roy et al, 2011;Mondal et al, 2018) further showed that the switching energy can be down to a scale of $ aJ/bit in a single nano-magnet on a piezoelectric (PE) substrate. Recently, Carman et al (Wang et al, 2018b) conceptualized an MTJ/FE structure which is controlled by SOT and ME effect. You et al (Su et al, 2019) theoretically predicted high performance in antiferromagnetic tunnel junction enabled hybrid structure where an applied E-field controls the strength of magnetoelastic anisotropy.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 Strains generated via the piezoelectric effects of a ferroelectric substrate under E-eld-controlled magnetic and electric properties is one of the most extensively used methods of ME coupling. 11,12 The PbMg 1/3 Nb 2/3 O 3 -PbTiO 3 (PMN-PT) substrate attracted considerable attention due to its high piezoelectric activity in FM/FE heterostructures, which is an ideal strain source. 13 The PMN-PT(011) substrate has largest ferroelastic domain switching and piezoelectric coefficients d 33 along the [01À1] direction, 14 which means E-eld along the [01À1] direction controls ME coupling in FM/PMN-PT(011) heterostructures more efficiently.…”
Section: Introductionmentioning
confidence: 99%